Donepezil transdermal patch and preparation method thereof

By using backing film, release film and drug-containing matrix layer containing donepezil, chemical penetration promoters and silicone-type pressure-sensitive glue matrix in the donepezil transdermal patch, the crystallization problem of existing transdermal patches is solved, and the stability and release speed are improved.

CN119632956APending Publication Date: 2025-03-18CHENGDU KANGHONG PHARMACEUTICAL GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311200822.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-18
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing donepezil transdermal patches are prone to crystallization after being placed, affecting stability and product quality.

Method used

The dotepipezil transdermal patch containing a backing film, a release film and a drug-containing matrix layer is used. The active ingredient donepezil, a chemical penetration promoter and a silicone-type pressure-sensitive glue matrix are added to the drug-containing matrix layer, and the active ingredient is evenly dispersed in the form of solid particles.

Benefits of technology

It has achieved a dopezil transdermal patch with no crystallization, excellent transdermal speed and good stability, and can maintain stable release for a long time (at least 7 days).

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004454029140000011
    Figure BDA0004454029140000011
  • Figure BDA0004454029140000091
    Figure BDA0004454029140000091
  • Figure BDA0004454029140000101
    Figure BDA0004454029140000101
Patent Text Reader

Abstract

The invention relates to a transdermal patch containing donepezil as an active ingredient and a preparation method of the transdermal patch, a drug-containing matrix layer of the patch contains donepezil, a chemical penetration enhancer and a silicone matrix, and the prepared transdermal patch can be stably released for a long time and is kept stable without devitrification.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of pharmaceutical preparations and relates to a transdermal absorption preparation containing donepezil. Background Art

[0002] Alzheimer's disease (AD), commonly known as senile dementia, is a degenerative disease of the central nervous system characterized by progressive cognitive impairment and memory loss. It is not only accompanied by neurological disorders, but also causes various complications such as depression and hyperosmolarity.

[0003] Most of the Alzheimer's disease treatment agents used are acetylcholinesterase inhibitors, including Donepezil (trade name: Aricept), Rivastigmin (trade name: Essen), Galantamine (trade name: Liyiling), etc. Among them, Donepezil was approved by the U.S. Food and Drug Administration (FDA) in 1996 for the treatment of mild and moderate Alzheimer's disease. Its chemical structure is as follows:

[0004]

[0005] The currently used donepezil preparations are in the form of tablets, capsules, etc., and are administered orally. However, for Alzheimer's patients, oral medications have problems such as difficulty remembering to take the medication and difficulty swallowing. Therefore, transdermal patches have become the first choice for clinical applications. The drugs in the patches can be absorbed by the human body by penetrating the skin, providing good medication convenience for Alzheimer's patients, and also avoiding the gastrointestinal discomfort caused by oral medications and the problem of difficulty swallowing in some patients, which can effectively improve patient compliance.

[0006] In the prior art, ethyl acetate is mostly used as a solvent when preparing donepezil transdermal patches, and the API is completely dissolved in the transdermal patch. However, the inventors found in a specific experimental process that such transdermal patches will exhibit obvious crystallization after being placed, causing stability problems and affecting product quality. Summary of the invention

[0007] The object of the present invention is to provide a donepezil transdermal patch which does not crystallize, has excellent skin penetration rate, good stability and / or can maintain stable release for a long time (at least 7 days) and a preparation method thereof.

[0008] The first object of the present invention is to provide a donepezil transdermal patch, wherein the transdermal patch comprises a backing film, a release film and a drug-containing matrix layer, wherein the drug-containing matrix layer contains an active ingredient donepezil, a chemical penetration enhancer, and a silicone pressure-sensitive adhesive matrix. The active ingredient is uniformly dispersed in the matrix in the form of solid particles. The content in the present invention is a weight percentage. It is well known in the art that the pressure-sensitive adhesive used during use is usually a wet glue with a certain silicone pressure-sensitive adhesive solid content (for example, BIO-PSA AC7-4301 solid content 70%, BIO-PSA AC7-4301 solid content 74%, BIO-PSA AC7-4201 solid content 70%), so the weight of the silicone pressure-sensitive adhesive matrix is ​​calculated by its solid content weight.

[0009] The content of the active ingredient in the patch of the present invention is 1.0-20.0% by weight. In certain embodiments, the content of the active ingredient is 1.0-15.0% by weight. In certain embodiments, the content of the active ingredient is 10.0-20.0% by weight. In certain embodiments, the content of the active ingredient is 10.0-15.0% by weight. In certain embodiments, the content of the active ingredient is 11.0-14.0% by weight. In certain embodiments, the content of the active ingredient is 10.0% by weight. In certain embodiments, the content of the active ingredient is 12.0% by weight. In certain embodiments, the content of the active ingredient is 13.0% by weight. In certain embodiments, the content of the active ingredient is 14.0% by weight. In certain embodiments, the content of the active ingredient is 10.9% by weight. In certain embodiments, the content of the active ingredient is 11.8% by weight. In certain embodiments, the content of the active ingredient is 13.3% by weight. In certain embodiments, the content of the active ingredient is 13.6% by weight.

[0010] The content of the silicone pressure-sensitive adhesive matrix in the patch of the present invention is 40.0-90.0% by weight, preferably 60.0-80.0% by weight, preferably 67.0-76.0% by weight, preferably 69.0-76.0% by weight, preferably 70.0-76.0% by weight, preferably 70.0% by weight, preferably 69.4% by weight, preferably 76.1% by weight, preferably 76.1% by weight, preferably 69.5% by weight.

[0011] Further, the penetration enhancer can be selected from one or more of polymers, ethers, fatty alcohols, fatty acids, and esters. In some embodiments, the penetration enhancer is a combination of polymers and fatty acids. The penetration enhancer includes but is not limited to ethyl cellulose, hydroxypropyl methylcellulose, povidone, copolyvidone, cross-linked polyvidone, 1-dodecyl-2-pyrrolidone, diethylene glycol ethyl ether, Bian Ze Brij including Bian Ze 30 and Bian Ze 52, triacetin, monoolein, isopropyl acetate, isopropyl palmitate, isopropyl laurate, glycerol, propylene glycol, octyl lauryl alcohol, hexadecanol, oleyl alcohol, benzyl alcohol, C8-C18 chain fatty acids, such as caprylic acid, myristic acid, oleic acid, lauric acid, one or more. In some embodiments, the penetration enhancer is C8-C18 chain fatty acids, Brij30, triacetin, isopropyl laurate, isopropyl palmitate, oil In some embodiments, the penetration enhancer is selected from one or more of C8-C18 chain fatty acids, Brij30, triacetin, oleyl alcohol, and cross-linked polyvinylpyrrolidone. In some embodiments, the penetration enhancer is one or more of cross-linked polyvinylpyrrolidone, Brij30, oleyl alcohol, and C8-C18 chain fatty acids. In some embodiments, the penetration enhancer is one or more of cross-linked polyvinylpyrrolidone and C8-C18 chain fatty acids. In some embodiments, the penetration enhancer is one or more of cross-linked polyvinylpyrrolidone, caprylic acid, myristic acid, oleic acid, and lauric acid. In some embodiments, the penetration enhancer is one or more of cross-linked polyvinylpyrrolidone and C12-C18 chain fatty acids, preferably one or more of cross-linked polyvinylpyrrolidone, myristic acid, oleic acid, and lauric acid, and preferably a combination of cross-linked polyvinylpyrrolidone and myristic acid.

[0012] The content of the penetration enhancer of the present invention is 5.0-30.0% by weight. In some embodiments, the content of the penetration enhancer is 5.0-25.0% by weight. In some embodiments, the content of the penetration enhancer is 5.0-22.0% by weight. In some embodiments, the content of the penetration enhancer is 5.0%-15.0% by weight. In some embodiments, the content of the penetration enhancer is 5.0-11.0% by weight. In some embodiments, the content of the penetration enhancer is 5.0-8.0% by weight. In some embodiments, The content of the penetration enhancer is 5.0-6.0% by weight. In some embodiments, the content of the penetration enhancer is 10.0-30.0% by weight. In some embodiments, the content of the penetration enhancer is 10.0-25.0% by weight. In some embodiments, the content of the penetration enhancer is 13.0-15.0% by weight. In some embodiments, the content of the penetration enhancer is 16.0-25.0% by weight. In some embodiments, the content of the penetration enhancer is 16.0-22.0% by weight. In some embodiments , the content of the penetration enhancer is 13.0-15.0% by weight, in some embodiments, the content of the penetration enhancer is 5.0-10.0% by weight, in some embodiments, the content of the penetration enhancer is 7.0-9.0% by weight, in some embodiments, the content of the penetration enhancer is 5.0% by weight, in some embodiments, the content of the penetration enhancer is 6.0% by weight, in some embodiments, the content of the penetration enhancer is 7.0% by weight, in some embodiments, the content of the penetration enhancer is 8.0% by weight In some embodiments, the content of the penetration enhancer is 9.0% by weight, in some embodiments, the content of the penetration enhancer is 13.0% by weight, in some embodiments, the content of the penetration enhancer is 14.0% by weight, in some embodiments, the content of the penetration enhancer is 15.0% by weight, in some embodiments, the content of the penetration enhancer is 16.0% by weight, in some embodiments, the content of the penetration enhancer is 13.6% by weight, in some embodiments, the content of the penetration enhancer is 22.0% by weight.

[0013] The content of the polymer penetration enhancer of the present invention is 5.0-30.0%, 5.0-20.0%, preferably 5.0-15.0%, preferably 7.0-15.0%, preferably 7.0-11.0%, preferably 7.0-9.0%, preferably 7.0%, 8.0%, 9.0%, 8.3%, 7.3%, 9.4% by weight.

[0014] The content of the ester penetration enhancer of the present invention is 5.0-10.0% by weight, preferably 5.0-8.0%, preferably 5.0-6.0%, preferably 5%, 5.4% or 6%.

[0015] The content of the fatty alcohol penetration enhancer of the present invention is 5.0-10.0% by weight, preferably 5.0-8.0%, preferably 5.0-6.0%, preferably 5.0%, 5.4% or 6.0%.

[0016] The content of the fatty acid penetration enhancer of the present invention is 5.0-15.0% by weight, preferably 5.0-10.0%, preferably 5.0-8.0%, preferably 5.0-6.0%, preferably 5.0%, 5.6%, 5.7%, 6.0%.

[0017] The content of the ether penetration enhancer of the present invention is 5.0-15.0% by weight, preferably 5.0-10.0% by weight, preferably 5.0%, 5.4%, 10.0% or 10.8% by weight.

[0018] Further, after screening a large number of antioxidants, the inventors of the present application found that the antioxidant can be selected from organic acids, amino acids, inorganic bases, esters, polyphenols, ethylene glycols, sulfites, resins, and others, including but not limited to citric acid, tartaric acid, fumaric acid, myristic acid, lactic acid, lauric acid, palmitic acid, sodium metabisulfite, sodium sulfite, ascorbyl palmitate, lysine, arginine, sodium bicarbonate, Eudragit E100, aluminum hydroxide, disodium ethylenediaminetetraacetate (EDTA), propyl gallate, butylated p-hydroxyanisole, butylated hydroxytoluene, tert-butylhydroquinone, ascorbic acid, isovitamin C, ascorbyl palmitate, pyrosulfite. One or more of sodium, lauryl lactate, etc., preferably one or more of amino acids, esters, inorganic bases, sulfites, resins, preferably one or more of sodium metabisulfite, sodium sulfite, ascorbyl palmitate, lysine, arginine, sodium bicarbonate, Eudragit E100, and aluminum hydroxide, preferably one or more of sodium metabisulfite, sodium sulfite, ascorbyl palmitate, lysine, arginine, sodium bicarbonate, Eudragit E100, preferably one or more of sodium metabisulfite, sodium sulfite, ascorbyl palmitate, lysine, arginine, sodium bicarbonate, Eudragit E100, preferably one or more of sodium metabisulfite, sodium sulfite, ascorbyl palmitate, lysine, and arginine, preferably one or more of ascorbyl palmitate, lysine, and arginine, more preferably arginine.The content of the antioxidant is 0.0% to 5.0% by weight. In some embodiments, the content of the antioxidant is 0.001% to 5.0% by weight. In some embodiments, the content of the antioxidant is 0.001% to 4.0% by weight. In some embodiments, the content of the antioxidant is 0.001% to 3.0% by weight. In some embodiments, the content of the antioxidant is 0.04% to 4.0% by weight. In some embodiments, the content of the antioxidant is 1% to 4.0% by weight. In some embodiments, the content of the antioxidant is 0.04% to 3.0% by weight. In some embodiments, the content of the antioxidant is 0.04% to 2.0% by weight. In some embodiments, the content of the antioxidant is 0.04% to 0.2% by weight. In some embodiments, the content of the antioxidant is In some embodiments, the content of the antioxidant is 1.0-5.0% by weight. In some embodiments, the content of the antioxidant is 2.0-4.0% by weight. In some embodiments, the content of the antioxidant is 2.0-3.0% by weight. In some embodiments, the content of the antioxidant is 0.0001% by weight. In some embodiments, the content of the antioxidant is 0.001% by weight. In some embodiments, the content of the antioxidant is 0.01% by weight. In some embodiments, the content of the antioxidant is 0.04% by weight. In some embodiments, the content of the antioxidant is 0.2% by weight. In some embodiments, the content of the antioxidant is 2.0% by weight. In some embodiments, the content of the antioxidant is 3.0% or 2.7% by weight. In some embodiments, the content of the antioxidant is 4.0% by weight.

[0019] Furthermore, the present invention provides a transdermal patch comprising the following components and their weight percentages:

[0020] Donepezil: 1.0-20.0%

[0021] Chemical penetration enhancer: 5.0~30.0%

[0022] Antioxidant: 0.0%~5.0%

[0023] Silicone pressure-sensitive adhesive: 60.0% to 80.0%

[0024] The chemical penetration enhancer is selected from one or more of polymers, ethers, fatty alcohols, fatty acids, and esters, preferably one or more of C8-C18 chain fatty acids, Brij30, triacetin, oleyl alcohol, and cross-linked polyvinylpyrrolidone, preferably one or more of cross-linked polyvinylpyrrolidone, Brij30, oleyl alcohol, and C8-C18 chain organic acids, preferably one or more of cross-linked polyvinylpyrrolidone and C8-C18 chain organic acids, preferably one or more of cross-linked polyvinylpyrrolidone, caprylic acid, myristic acid, oleic acid, and lauric acid, preferably cross-linked polyvinylpyrrolidone and myristic acid; the antioxidant is selected from one or more of sodium metasulfite, sodium sulfite, ascorbyl palmitate, lysine, arginine, sodium bicarbonate, and Eudragit E100, preferably one or more of sodium metasulfite, sodium sulfite, ascorbyl palmitate, lysine, and arginine, preferably one or more of ascorbyl palmitate, lysine, and arginine, preferably arginine.

[0025] Furthermore, the transdermal patch contains the following components and contents:

[0026] Donepezil: 10.0-20.0%

[0027] Chemical penetration enhancer: 5.0~22.0%

[0028] Antioxidant: 0.001%~4.0%

[0029] Silicone pressure-sensitive adhesive: 67.0-76.0%

[0030] Furthermore, the transdermal patch contains the following components and contents:

[0031] Donepezil: 10.0-20.0%

[0032] Chemical penetration enhancer: 13.0~22.0%

[0033] Antioxidant: 0.001%~4.0%

[0034] Silicone pressure-sensitive adhesive: 67.0-76.0%

[0035] Furthermore, the transdermal patch contains the following components and contents:

[0036] Donepezil: 10.0-14.0%

[0037] Fatty acids, fatty alcohols, esters, ethers, or polymers: 5.0-22.0%

[0038] Antioxidant: 0.001%~4.0%

[0039] Silicone pressure-sensitive adhesive: 69.0-76.0%

[0040] Furthermore, the transdermal patch contains the following components and contents:

[0041] Donepezil: 10.0-14.0%

[0042] Fatty acids, fatty alcohols or ethers: 5.0-10.0%

[0044] Polymer penetration enhancers: 7.0-11.0%

[0045] Antioxidant: 0.001%~4.0%

[0046] Silicone pressure-sensitive adhesive: 69.0-76.0%

[0047] Furthermore, the transdermal patch contains the following components and contents:

[0048] Donepezil: 10.0-14.0%

[0049] Fatty acids, fatty alcohols or ethers: 5.0-6.0%

[0051] Polymer penetration enhancers: 7.0-10.0%

[0052] Antioxidant: 2.0%~4.0%

[0053] Silicone pressure-sensitive adhesive: 69.0-76.0%

[0054] Furthermore, the transdermal patch contains the following components and contents:

[0055] Donepezil: 10.0-14.0%

[0056] Fatty acid penetration enhancer: 5.0-6.0%

[0057] Polymer penetration enhancers: 7.0-10.0%

[0058] Arginine: 2.0% to 4.0%

[0059] Silicone pressure-sensitive adhesive: 69.0-76.0%

[0060] Furthermore, the transdermal patch contains the following components and contents:

[0061] Donepezil: 11.0-14.0%

[0062] Myristic acid: 5.0-6.0%

[0063] Cross-linked polyvinylpyrrolidone: 7.0-9.0%

[0064] Arginine: 3.0%

[0065] Silicone pressure-sensitive adhesive: 69.0-76.0%

[0066] Furthermore, the transdermal patch contains the following components and contents:

[0067] Donepezil: 13.6%

[0068] Myristic acid: 5.7%

[0069] Crospovidone: 8.3%

[0070] Arginine: 3%

[0071] Silicone pressure-sensitive adhesive: 69.4%

[0072] The transdermal patch contains the following components and contents:

[0073] Donepezil: 13.6%

[0074] Myristic acid: 5.6%

[0075] Crospovidone: 8.3%

[0076] Arginine: 3.1%

[0077] Silicone pressure-sensitive adhesive: 69.4%.

[0078] The present invention further provides a method for preparing a donepezil transdermal patch, comprising the following steps: adding a solvent to a prescribed amount of API and excipients other than a pressure-sensitive adhesive, mixing, then adding a pressure-sensitive adhesive, mixing, obtaining a glue solution, applying the glue solution on a release film to form a wet glue, drying, and pressing a backing film to obtain a finished product. The solvent of the present invention can evenly disperse the raw materials so that they exist in the form of solid particles, and finally volatilize during the preparation of the patch. The solvent is selected from one or more of heptane, ethanol, n-hexane, cyclohexane, and n-propanol, preferably heptane, and in certain embodiments, the heptane content is 3-7.5ml. DETAILED DESCRIPTION

[0079] The present invention is further described in detail by the following examples, which are not intended to limit the scope of protection of the present invention.

[0080] In the following specific implementations, the drugs, reagents and instruments used are as follows:

[0081] Instruments and equipment: High performance liquid chromatograph (LC-20A, Shimadzu); transdermal diffusion tester (TK-12H, Shanghai Kaikai Technology and Trading Co., Ltd.); heated automatic coating machine (BEVS1811 / 3, Guangzhou Shenghua Industrial Co., Ltd.); blast drying oven (DHG-9246A, Shanghai Jinghong Experimental Equipment Co., Ltd.).

[0082] Drugs and reagents: Donepezil hydrochloride (Apotex); silicone pressure-sensitive adhesive (BIO-PSAAC7-4301 containing 70% solid content, BIO-PSAAC7-4201 containing 70% solid content, Dow Corning); Brij 52 (Aladdin Reagent Co., Ltd.), Brij 30 (Aladdin Reagent Co., Ltd.); ethyl acetate (Chengdu Kelong Chemical Co., Ltd.); n-heptane (Chengdu Kelong Chemical Co., Ltd.); myristic acid (Kewell Company), caprylic acid (Kewell Company); lauric acid (Kewell Company); triacetin (Jiangsu Ruijia Chemical Co., Ltd.); oleic acid (Chengdu Kelong Chemical Co., Ltd.); arginine (PanReacApplichem); lysine (Aladdin Reagent Co., Ltd.); histidine (Aladdin Reagent Co., Ltd.); ascorbyl palmitate (Aladdin Reagent Co., Ltd.); sodium sulfite (Chengdu Kelong Chemical Reagent Factory); sodium metabisulfite (Chengdu Huayi Pharmaceutical Excipient Manufacturing Co., Ltd.); sodium bicarbonate (Chengdu Kelong Chemical Reagent Factory); aluminum hydroxide (Shijiazhuang Wuyue Pharmaceutical Factory); cross-linked polyvinylpyrrolidone (BASF). Among them, silicone pressure-sensitive adhesive is wet adhesive, which needs to be converted into total weight according to its solid content.

[0083] Packaging material: SCOTCHPAK 1022PET FILM, SCOTCHPAK 9733, SCOTCHPAK 9709 (3M Company).

[0084] Donepezil can be prepared according to conventional methods and prior art methods, or according to the following preparation method:

[0085] Weigh 50g of donepezil hydrochloride and pour it into a round-bottom flask, then add 300ml of water to dissolve it. After it is basically clarified, then dissolve 50g of sodium carbonate in 200ml of pure water and drop it into the flask. White suspended matter appears, then add 800ml of ethyl acetate and stir at room temperature; use a separatory funnel to separate the mixed solution, concentrate the upper ethyl acetate at 35°C under reduced pressure, extract the lower aqueous phase with 200ml of ethyl acetate twice, combine the organic phases, and concentrate under reduced pressure; slowly add 160ml of water to 350ml of methanol to obtain a light yellow solid solution obtained by concentration. During this process, white floccules are precipitated. Stir at room temperature overnight, filter the suspended matter, and dry it with air at 50°C.

[0086] The preparation process, in vitro skin permeation test and stability test methods in the following examples are as follows:

[0087] Preparation process: Add the prescribed amount of API and auxiliary materials except pressure-sensitive adhesive into the solvent, mix, then add the pressure-sensitive adhesive, mix to obtain adhesive solution, apply the adhesive solution on the release film to form wet adhesive, dry at 40-90℃, and press with a backing film to obtain the finished product.

[0088] In vitro transdermal experiment: Take the back skin of commercially available 1.5-month-old Bama Xiang pigs, carefully remove the subcutaneous fat (skin thickness is generally less than 1mm), thaw and place in 60-degree purified water for 1 minute, filter paper to absorb the moisture. Use a horizontal diffusion cell with an effective diffusion area of ​​1.44cm2 and a volume of 4ml for skin flux research. Place the skin between the donor and receptor compartments of the diffusion cell. Add pH7.220*PBS solution diluted with 30% ethanol aqueous solution to the receiving compartment, stir at 200rpm, keep the temperature at 32±0.5 degrees, take 4ml samples from the receiving solution regularly (4h, 8h, 24h, 48h, 72h, 96h, 120h, 144h, 168h), and replace the receiving solution with fresh phosphate buffer. HPLC was used to measure the amount of medicine in the receiving solution at each time point and calculate the penetration rate.

[0089] Room temperature stability study: Each prescription was placed naked at room temperature for 12 days, and the cross-influence caused by other conditions was avoided as much as possible. The conventional HPLC detection method was used for detection, with the total impurity content as the indicator.

[0090] High temperature 60 degree stability study: Each prescription was placed naked at high temperature (60°C) for 10 days, and the cross-influence caused by other conditions was avoided as much as possible. The conventional HPLC detection method was used for detection, and the total impurity content was used as an indicator.

[0091] The data in the examples are the average values ​​of three experiments and are all statistically significant.

[0092] Example 1 Prescription 1 was prepared as shown in Table 1 (only the antioxidant was kept to three decimal places, and the rest were kept to one decimal place):

[0093] Table 1

[0094] Components Content by weight Donepezil 13.4% Triacetin 4.2% Sodium metasulfite 0.042% Ascorbyl Palmitate 0.003% Sodium sulfite 0.2% Crospovidone 11.4% BIO-PSAAC7-4301 70.7% Ethyl acetoate 6ml

[0095] Crystallization results: After the sample of prescription 1 was placed at room temperature for 30 days, white crystals appeared.

[0096] Example 2 Prescription 2 is shown in Table 2 (only the antioxidant is retained to three decimal places, and the rest are retained to one decimal place):

[0097] Table 2

[0098] Components Content by weight Donepezil 13.4% Triacetin 4.2% Sodium metasulfite 0.042% Ascorbyl Palmitate 0.003% Sodium sulfite 0.2% Crospovidone 11.4% BIO-PSAAC7-4301 70.7% n-Heptane 6ml

[0099] In vitro transdermal results: Prescription 2 was subjected to an in vitro transdermal test, and the results are shown in Table 3:

[0100] Table 3

[0101] Time / h Prescription 2 168h penetration rate (μg / cm2 / h) 3.9

[0102] Crystallization results: After the sample of prescription 2 was placed at room temperature for 30 days, no crystallization occurred. Subsequent experiments were conducted to optimize the excipients and improve the transdermal speed while ensuring that all prescriptions did not crystallize.

[0103] Example 3 Prescriptions 3-5 are shown in Table 4:

[0104] Table 4

[0105] Components Prescription 3 Prescription 4 Prescription 5 Donepezil 10.9% 10.9% 10.9% Triacetin 5.4% / / Oleyl alcohol / 5.4% / Brij30 5.4% 5.4% 5.4% Brij52 / / 5.4% Crospovidone 10.9% 10.9% 10.9% n-Heptane 6ml 6ml 6ml BIO-PSAAC7-4301 67.4% 67.4% 67.4%

[0106] In vitro transdermal results: Prescriptions 3-5 were subjected to in vitro transdermal experiments. The results are shown in Table 5:

[0107] Table 5

[0108] Prescription 3 Prescription 4 Prescription 5 168h Transdermal speed (μg / cm2 / h) 8.9 8.9 5.4

[0109] Example 4 Prescriptions 6-11 are shown in Table 6:

[0110] Table 6

[0111]

[0112] In vitro transdermal results: Prescriptions 6-11 were subjected to in vitro transdermal tests. The results are shown in Table 7:

[0113] Table 7

[0114]

[0115]

[0116] Example 5 Prescriptions 12-16 are shown in Table 8:

[0117] Table 8

[0118] Prescription 12 Prescription 13 Prescription 14 Prescription 15 Prescription 16 Donepezil 13.6% 13.6% 13.6% 13.6% 13.6% Myristic acid 5.7% 5.7% 5.7% 5.7% 5.7% Crospovidone 11.3% 8.3% 8.3% 8.3% 8.3% Sodium bicarbonate / 3.0% / / / Eudragit E100 / / 3.0% / / Aluminum hydroxide / / / 3.0% / Arginine / / / / 3.0% n-Heptane 7.5ml 7.5ml 7.5ml 7.5ml 7.5ml BIO-PSAAC7-4301 69.4% 69.4% 69.4% 69.4% 69.4%

[0119] Stability results: Prescriptions 12-16 were subjected to stability tests, and the results are shown in Table 9:

[0120] Table 9

[0121]

[0122] When the antioxidant was replaced with a combination of disodium bicarbonate and potassium dihydrogen carbonate or a combination of disodium bicarbonate and sodium dihydrogen carbonate, cracks appeared on the tablets at day 0.

[0123] Example 6 Prescriptions 17-23 are shown in Table 10 (wherein the antioxidants in prescriptions 18 / 19 are retained to two or three decimal places, and the rest are retained to one decimal place):

[0124] Table 10

[0125]

[0126]

[0127] Stability results: Prescriptions 17-23 were subjected to stability tests, and the results are shown in Table 11:

[0128] Table 11

[0129]

[0130] Example 7 Prescriptions 24-27 are shown in Table 12:

[0131] Table 12

[0132] Prescription 24 Prescription 25 Prescription 26 Prescription 27 API 13.6% 13.6% 13.6% 13.6% Myristic acid 5.6% 5.6% 5.6% 5.6% CL-M 10.4% 9.4% 8.3% 7.3% Arginine 1.0% 1.9% 3.1% 4.0% n-Heptane 6ml 6ml 6ml 6ml BIO-PSAAC7-4301 69.4% 69.5% 69.4% 69.5%

[0133] In vitro transdermal results: Prescriptions 24-27 were subjected to in vitro transdermal tests. The results are shown in Table 13:

[0134] Table 13

[0135] Prescription 24 Prescription 25 Prescription 26 Prescription 27 168h Transdermal speed (μg / cm2 / h) 15.243 10.102 9.651 7.911

[0136] Stability results: Prescriptions 24-27 were subjected to stability tests, and the results are shown in Table 14:

[0137] Table 14

[0138]

[0139]

Claims

1. A donepezil transdermal patch comprising a backing layer, a drug-containing matrix layer, and a peeling layer, characterized in that The drug-containing matrix layer comprises (i) donepezil as an active ingredient, (ii) a silicone-type pressure-sensitive adhesive matrix, and (iii) a chemical penetration enhancer. The active ingredient is uniformly dispersed in the matrix in the form of solid particles.

2. The patch according to claim 1, characterized in that The content of donepezil in the patch is 1.0 to 20.0% by weight, preferably 10.0 to 20.0% by weight, preferably 10.0 to 14.0% by weight, and preferably 13.3% or 13.6% by weight.

3. The transdermal patch according to claim 1, characterized in that The penetration enhancer is selected from one or more of polymers, ethers, fatty alcohols, fatty acids, and esters, preferably a combination of polymers and fatty acids.

4. The transdermal patch according to claim 3, characterized in that The penetration enhancer is selected from one or more of C8-C18 chain fatty acids, Brij30, triacetin, isopropyl laurate, isopropyl palmitate, oleyl alcohol, cross-linked polyvinylpyrrolidone, polyvinylpyrrolidone, and copolyvinylpyrrolidone. Preferably, the penetration enhancer is selected from one or more of C8-C18 chain fatty acids, Brij30, triacetin, oleyl alcohol, and cross-linked polyvinylpyrrolidone. Preferably, the penetration enhancer is cross-linked polyvinylpyrrolidone, Brij30, oleyl alcohol, and one or more of C8-C18 chain fatty acids. Preferably, the penetration enhancer is cross-linked polyvinylpyrrolidone and one or more of C8-C18 chain fatty acids. Preferably, the penetration enhancer is cross-linked polyvinylpyrrolidone, caprylic acid, myristic acid, oleyl alcohol. Acid, lauric acid or one or more, preferably the penetration enhancer is cross-linked polyvinylpyrrolidone and myristic acid, preferably the content of the penetration enhancer is 5.0-30.0% by weight, preferably 5.0-22.0%, preferably 13.0-22.0%, preferably 13.0-15.0%, preferably 13.6% or 14.0%, preferably the content of the polymer penetration enhancer is 5.0-15.0% by weight, preferably 7.0-11.0%, preferably 7.0-9.0%, preferably 8.0% or 8.3%, preferably the content of the fatty acid penetration enhancer is 5.0-15.0% by weight, preferably 5.0-10.0%, preferably 5.0-6.0%, preferably 5.6%.

5. The transdermal patch according to claim 3, characterized in that The patch contains an antioxidant, and preferably the antioxidant is selected from one or more of amino acids, esters, inorganic bases, sulfites, and resins, preferably one or more of sodium metabisulfite, sodium sulfite, ascorbyl palmitate, lysine, arginine, sodium bicarbonate, and Eudragit E100, preferably one or more of sodium bicarbonate, Eudragit E100, ascorbyl palmitate, lysine, and arginine, more preferably one or more of ascorbyl palmitate, lysine, and arginine, more preferably arginine, and the content of the antioxidant is preferably 0.0-5.0% by weight, preferably 0.001-4.0%, preferably 0.001%-3.0%, preferably 2.0%-4.0%, preferably 3.0%.

6. The transdermal patch according to claim 1, characterized in that The content of the silicone pressure-sensitive adhesive matrix is ​​40.0-90.0% by weight, preferably 60.0-80.0%, preferably 67.0-76.0%, preferably 69.0-76.0%, preferably 70.1 or 69.4% by weight.

7. The transdermal patch according to any one of claims 1 to 6, characterized in that Contains the following components and contents: Donepezil: 1.0-20.0% Chemical penetration enhancer: 5.0~30.0% Antioxidant: 0.0%~5.0% Silicone pressure-sensitive adhesive: 60.0% to 80.0% The chemical penetration enhancer is selected from one or more of polymers, ethers, fatty alcohols, fatty acids, and esters, preferably one or more of C8-C18 chain fatty acids, Brij30, triacetin, oleyl alcohol, and cross-linked polyvinylpyrrolidone, preferably one or more of cross-linked polyvinylpyrrolidone, Brij30, oleyl alcohol, and C8-C18 chain organic acids, preferably one or more of cross-linked polyvinylpyrrolidone and C8-C18 chain organic acids, preferably one or more of cross-linked polyvinylpyrrolidone, caprylic acid, myristic acid, oleic acid, and lauric acid, preferably cross-linked polyvinylpyrrolidone and myristic acid; the antioxidant is selected from one or more of sodium metabisulfite, sodium sulfite, ascorbyl palmitate, lysine, arginine, sodium bicarbonate, and Eudragit E100, preferably one or more of sodium metabisulfite, sodium sulfite, ascorbyl palmitate, lysine, and arginine, preferably one or more of ascorbyl palmitate, lysine, and arginine, preferably arginine, and the transdermal patch preferably contains the following components and contents: Donepezil: 10.0-20.0% Chemical penetration enhancer: 13.0~22.0% Antioxidant: 0.001%~4.0% Silicone pressure-sensitive adhesive: 67.0-76.0%, Preferably, the transdermal patch contains the following components and contents: Donepezil: 10.0-14.0% Fatty acids or fatty alcohols or esters or ethers Or polymer penetration enhancers: 5.0-22.0% Antioxidant: 0.001%~4.0% Silicone pressure-sensitive adhesive: 69.0-76.0%, Preferably, the transdermal patch contains the following components and contents: Donepezil: 10.0-14.0% Fatty acids, fatty alcohols or ethers: 5.0-10.0% Polymer penetration enhancers: 7.0-11.0% Antioxidant: 0.001%~4.0% Silicone pressure-sensitive adhesive: 69.0-76.0%, Preferably, the transdermal patch contains the following components and contents: Donepezil: 10.0-14.0% Fatty acids, fatty alcohols or ethers: 5.0-6.0% Polymer penetration enhancers: 7.0-10.0% Antioxidant: 2.0%~4.0% Silicone pressure-sensitive adhesive: 69.0-76.0%, Preferably, the transdermal patch contains the following components and contents: Donepezil: 10.0-14.0% Fatty acid penetration enhancer: 5.0-6.0% Polymer penetration enhancers: 7.0-10.0% Arginine: 2.0% to 4.0% Silicone pressure-sensitive adhesive: 69.0-76.0%, Preferably, the transdermal patch contains the following components and contents: Donepezil: 11.0-14.0% Myristic acid: 5.0-6.0% Cross-linked polyvinylpyrrolidone: 7.0-9.0% Arginine: 3.0% Silicone pressure-sensitive adhesive: 69.0-76.0%, Preferably, the transdermal patch contains the following components and contents: Donepezil: 13.6% Myristic acid: 5.7% Crospovidone: 8.3% Arginine: 3% Silicone pressure-sensitive adhesive: 69.4% or Donepezil: 13.6% Myristic acid: 5.6% Crospovidone: 8.3% Arginine: 3.1% Silicone pressure-sensitive adhesive: 69.4%.

8. A method for preparing the donepezil transdermal patch according to any one of claims 1 to 19, characterized in that The method comprises the following steps: adding a prescribed amount of API and auxiliary materials except the pressure-sensitive adhesive into a solvent, mixing, then adding the pressure-sensitive adhesive, mixing to obtain a glue solution, coating the glue solution on a release film to form a wet glue, drying, and pressing with a backing film to obtain a finished product. Preferably, the solvent is selected from one or more of heptane, ethanol, n-hexane, cyclohexane, and n-propanol, preferably heptane.